2011
DOI: 10.1111/j.1537-2995.2011.03396.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of SLC44A2 alleles encoding human neutrophil antigen‐3 variants in the African American population

Abstract: Background The human neutrophil antigen-3 (HNA-3) epitopes reside on the choline transporter-like protein-2 (CTL2). A single-nucleotide substitution (461G>A; Arg154Gln) on the CTL2 gene (SLC44A2) defines the allele SLC44A2*1, which expresses HNA-3a, and SLC44A2*2, which expresses HNA-3b; an additional substitution (457C>T; Leu153Phe) in SLC44A2*1:2 may impact genotyping systems. People who only express HNA-3b may develop anti-HNA-3a. These alloantibodies have been linked to severe transfusion-related acute lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
43
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 22 publications
10
43
3
Order By: Relevance
“…The HNA‐3b/3b genotype frequency among the Zhuang population is 8.6%, which is similar to the frequencies reported in the Dong population of our study and also other Asian populations like Chinese Han, Japanese and Thai shown by previous publications (Changsri et al., ; Matsuhashi et al., ; Xia et al., ) but is significantly higher than that of African American Shown by Huvard et al. (), Brazilian as shown by Lopes et al. () and also English Caucasian populations as revealed by Cardoso et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The HNA‐3b/3b genotype frequency among the Zhuang population is 8.6%, which is similar to the frequencies reported in the Dong population of our study and also other Asian populations like Chinese Han, Japanese and Thai shown by previous publications (Changsri et al., ; Matsuhashi et al., ; Xia et al., ) but is significantly higher than that of African American Shown by Huvard et al. (), Brazilian as shown by Lopes et al. () and also English Caucasian populations as revealed by Cardoso et al.…”
Section: Discussionsupporting
confidence: 91%
“…(), but higher than the African Americans (0.04%) as reported by Huvard et al. (), showing the different potentials of inducing TRALI among different human populations.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…5). The HNA-3a encoding allele was demonstrated in Caucasians with a frequency of 0.79, in African Americans with 0.93 and in Chinese with 0.74, and the respective HNA-3b-encoding alleles with 0.21, 0.07 and 0.26 [82,83,84]. An additional SLC44A2*451C>T exchange (rs147820753) affecting the amino acid next to Arg152 and inducing a Leu151Phe substitution impairs the HNA-3a epitope in a way that the induction of neutrophil agglutination by some HNA-3a-specific alloantibodies is diminished or even abrogated [85].…”
Section: Hna-3mentioning
confidence: 99%
“…Of note is that this additional mutation can influence HNA-3a typing in HNA-3a/3b heterozygous individuals when the HNA-3a allele-specific sense primer binds with reduced affinity so that the typing result is falsely interpreted as HNA-3b homozygous. This methodical problem can be overcome by applying adequate molecular tests [83,86]. The SLC44A2*451C>T substitution has been demonstrated with a gene frequency of 0.01 and phenotype frequencies of 2.4% in the Caucasian population [80,85] and of 0.4% in African Americans [83].…”
Section: Hna-3mentioning
confidence: 99%